KONTRUKSI PERKARA PERUSAKAN FASILITAS PT. WIKARYA SAKTI PADA PROSES PERSIDANGAN DI PENGADILAN NEGERI JAMBI DIKAITKAN DENGAN TUJUAN KEBENARAN MATERIL - Khofifah Dinda Syahputri; Davit Rahmadan; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
District Court Decision Number 708/Pid.B/2019/PN.Jmb is one of the cases of nationalconcerm. Agrarian conflicts that occur between corporations and civil society often lead to thebringing of the case into criminal justice institutions. Prolonged conflicts cannot be resolved bythe government local area so that the conflict leads to a criminal incident, the agrarian conflictwhich is the root of the problem is forgotten and civil society is considered as an actor of thecriminal event of the Panel of Judges, in assessing the criminal event is seems as if they do notsee the causes of the criminal incident, because The decisions made sometimes omit animportant segment of the emergence of a criminal incident.The purpose of this study is how to apply the law and material truth in the constructionof cases of destruction of facilities and to find out the legal constructions of judges in decidingcases of damage to facilities at the Jambi District Court. The research method used in thisthesis uses normative legal research, namely legal research that examines regulations.Legislation and legal priciples I this normative research, the author conducted research onseveral court legal materials.From the results of this research, it can be conclude that the Judge’s Decision is astatement by the judges as a state official who is given the authority to do so, in the from of acriminal decision if the perpetrator’s actions are proven legally and convincingly guilty in aneffort to make decisions and impose criminal sanctions, of the course the judge hasconsiderations- considerations consisting of juridical considerations, including the indictmentof the Public Prosecutor, the demands of the Public Prosecutor, witness statement, testimony ofthe defendant, and sociological considerations covering the background of the defendant’sactions, the consequences of the defendant’s actions and the condition of the defendant at thetime of committing the act. Analyzing the judges’ considerations in this case, according to theauthor, the judge’s consideartions or judgments in this case are not objective because they arenot based on facts revealed at trial. And the judge has violated the mandate of article 5paragraph (1) Law number 48 of 2009 concerning Judicial Power which states that judges areobliged to explore, follow, and understand legal values and a sence of justice.Keywords : Legal Constructions of Judges, Applications of Law and Material Truth.